The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0103-84782002000300020
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de frangos de corte criados em diferentes densidades populacionais, no inverno, no Sul do Brasil

Abstract: RESUMOO trabalho teve por objetivo determinar a influência da densidade de 10, 12, 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
2
7
0
2
Order By: Relevance
“…No differences were observed since a small carcass has a smaller cut whereas a large carcass has a large cut, with the same percentage. These data are in accordance with those found by Mortari et al (2002), who assessed broiler chicken performance at four stocking densities (10, 12, 14, and 16 birds m ) and observed those densities affected carcass characteristics. Table 3.…”
Section: −2supporting
confidence: 92%
See 2 more Smart Citations
“…No differences were observed since a small carcass has a smaller cut whereas a large carcass has a large cut, with the same percentage. These data are in accordance with those found by Mortari et al (2002), who assessed broiler chicken performance at four stocking densities (10, 12, 14, and 16 birds m ) and observed those densities affected carcass characteristics. Table 3.…”
Section: −2supporting
confidence: 92%
“…Mortari et al (2002), studying the performance of broiler chickens reared at densities of 10, 12, 14, and 16 birds m , observed a decreased weight gain as the density increased. These authors concluded that feed intake and live weight were higher in birds reared at lower densities, but feed conversion and rearing viability showed no effect from stocking density, which was also observed in this study.…”
Section: −2mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Moreira et al (2004), evaluating three housing densities (10, 13, or 16 broilers/m 2 ), observed significant reduction in weight gain in birds housed at 10 and 16 birds/ m 2 . Mortari et al (2002) also reported reduced body weight as rearing density increased, and Thomas et al (2004), Dozier et al (2005a) *significant at 5%; **significant at 1%; means followed by different lowercase letters within a column are statistically different; means followed by different uppercase letters within a row are statistically different.…”
Section: Resultsmentioning
confidence: 91%
“…Dessa forma, esse tema foi alvo de várias pesquisas visando avaliar as melhores densidades de estocagem para diferentes espécies animais, em seu ambiente de criação, como aves em galpões (Mortari et al, 2002), suínos em baias (Banhazi et al, 2001), coelhos em gaiolas (Oliveira & Almeida, 2002), camarões em viveiros (Zimmerman & Raupp, 1992) e peixes em tanques e viveiros (Carneiro et al, 1999;Graeff & Pruner, 1999e 2000Vieira et al, 2000;Gomes & Schlindwein, 2000;Souza-Filho & Cerqueira, 2003;Cavero et al, 2003;Salaro et al, 2003). Embora esses estudos tenham sido realizados com espécies diferentes, várias conclusões devem ser verificadas e avaliadas na recria de rãs, observando-se as devidas particularidades.…”
Section: Introductionunclassified